Atrazine degradation by Bacillus safensis strain BUK_BCH_BTE6 isolated from agricultural land in northwestern Nigeria - Yakasai, Hafeez Muhammad; Muhammad, Faisal; Shukor, Mohd Yunus (Universitas Gadjah Mada, 2023)
Atrazine herbicide is known to disrupt the endocrine system and is potentially carcinogenic. Consumption of which is devastating. This research aimed to isolate and characterize bacteria with atrazine degrading ability. An enrichment method was adopted to isolate the bacteria on mineral salt media following serial dilution. The isolate was identified molecularly and characterized based on effects of temperature, pH, substrate concentration, incubation time, inoculum size and heavy metals. GC-MS analysis was performed to identify the metabolites and degradation efficiency. The isolate was identified as Bacillus safensis strain BUKˍBCHˍBTE6 based on 16S rRNA gene sequence and molecular phylogenetic analysis. Growth and degradation of atrazine by this bacterium was optimal at 35 °C, pH of 7.5, 400 mgL-1, inoculum size 600 µL after 48 h. The growth of the isolate was inhibited by 2 ppm Hg, Cd, Cr, Pb, Ar and Ni. The degradation efficiency after 120 h was 88.85%. GC-MS analysis detected the formation of Desethyldeisopropylatrazine, Deisopropylatrazine, N-Ethylammelide and Cyanuric acid as metabolites. This isolate can be efficient atrazine degrader, hence may be beneficial for bioremediation of atrazine polluted sites.